Taxonomic review of the rhinocryptid genus Eleoscytalopus (I): Bahia Tapaculo (E-psychopompus) is vocally and morphologically distinct from White-breasted Tapaculo (E-indigoticus) - Moraes, Leonardo Amaral de; Bornschein, Marcos Ricardo [UNESP]; Ferreira Rodrigues Gatto, Cassiano Augusto; Santos, Sidnei Sampaio dos; Mauricio, Giovanni Nachtigall (Amer Ornithologists Union, 2018)
The Bahia Tapaculo (Eleoscytalopus psychopompus) is a rare taxon endemic to a narrow strip of lowland Atlantic Forest in the coast of Bahia, Brazil. Its phenotypic distinction from its sister species, the White-breasted Tapaculo (E. indigoticus), has been considered doubtful because the supposed diagnostic plumage characters were proposed on the basis of only 3 specimens (the type series) and there were no vocal data for the Bahia Tapaculo. Given that it is classified as endangered globally according to IUCN criteria, the definition of the taxonomic status of the Bahia Tapaculo is fundamental for the adoption of effective conservation measures. We conducted analyses of plumage, morphometrics, and vocalizations of both Bahia and White-breasted tapaculos to test for the phenotypic distinction between them. We found that their songs differ significantly in 2 parameters, pace (no overlap) and frequency (slight overlap); and that their calls (both monosyllabic and multisyllabic calls) differ in multiple parameters, including note shape and structure. Plumage color and pattern differ in 4 aspects, including a prominent one, barred vs. unbarred flanks. We found a difference in wing: tail ratio, with no overlap, revealing that these taxa are proportioned differently, with the Bahia Tapaculo tending to have longer wings and shorter tail. These differences, besides the genetic distance and reciprocal monophyly, are of the same or greater magnitude than those found between several sister taxa accepted as biological species in the family Rhinocryptidae, thus supporting biological species status for the Bahia Tapaculo.
Keywords: Atlantic Forest; Bahia Tapaculo; endangered species; taxonomic revision; vocalizations